1983
DOI: 10.1007/bf00279945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthetic rat C-peptide in normal and diabetic rats

Abstract: The effects of synthetic rat C-peptide 1 and C-peptide 2 on plasma insulin and blood glucose concentrations in the rat were studied. Infusion of rat C-peptide (500 micrograms X h-1 X kg-1) diminished glucose induced increase of plasma insulin by 56% (15.2 +/- 0.9 versus 6.6 +/- 0.6 ng/ml, p less than 0.01, mean +/- SEM). Somatostatin infused at a rate of 50 micrograms X h-1 X kg-1 body weight inhibited glucose-induced insulin secretion by 33%. In the presence of a mixture of both C-peptides or somatostatin, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…In diabetic rats, supra-physiological concentrations of C-peptide prolonged the hypoglycaemic actions of insulin [46] and, later, using the euglycaemic clamp technique in STZ (streptozotocin)-induced diabetic rats, physiological concentrations of rat C-peptide were found to significantly augment the disposal and metabolic clearance rates for glucose [47]. This result was largely blocked by the NOS inhibitor l-NMMA (N Gmonomethyl-l-arginine), suggesting that these actions of C-peptide were mediated by NO.…”
Section: C-peptide and Glucose Handlingmentioning
confidence: 99%
“…In diabetic rats, supra-physiological concentrations of C-peptide prolonged the hypoglycaemic actions of insulin [46] and, later, using the euglycaemic clamp technique in STZ (streptozotocin)-induced diabetic rats, physiological concentrations of rat C-peptide were found to significantly augment the disposal and metabolic clearance rates for glucose [47]. This result was largely blocked by the NOS inhibitor l-NMMA (N Gmonomethyl-l-arginine), suggesting that these actions of C-peptide were mediated by NO.…”
Section: C-peptide and Glucose Handlingmentioning
confidence: 99%
“…The early augmented glomerular filtration may play a crucial role in the development of diabetic nephropathy, and inhibition of the diabetesinduced hyperfiltration have beneficial effects on delaying the progression of kidney damage 6 . C-peptide is secreted from the islets of Langerhans together with insulin in equimolar amounts, and has been shown to influence physiological processes 7 . Several studies have also shown renoprotective effects of exogenous C-peptide administration to patients with type-1 diabetes 8,9 , but also to animals with experimental insulinopenic diabetes 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the early 1980s, it was suggested that C-peptide may influence biological functions (59). Several recent studies have reported renoprotective effects of C-peptide when it is administered to patients with type 1 diabetes (13,19,20) and animal models of experimental insulinopenic diabetes (16,36,(47)(48)(49)51).…”
mentioning
confidence: 99%